а) ( -3 ) * ( - 2) * ( - 1 ) * 4 = - 24
( минус * минус = плюс; плюс * минус = минус
минус * плюс = минус знак минус)
( теперь можно все перемножить и поставить знак минус: 3 * 2 * 1 * 4 = 24 и знак минус)
- 3 * ( - 2 ) = 6
6 * ( - 1 ) = - 6
- 6 * 4 = - 24
б) ( -2 ) * 3 * ( -4 ) * ( -6 ) = - 144
( минус * плюс = минус; минус * минус = плюс; плюс * минус = минус)
( 2 * 3 * 4 * 6 = 144 и знак минус)
- 2 * 3 = - 6
- 6 * ( - 4 ) = 24
24 * ( - 6 ) = - 144
а) ( -3 ) * ( - 2) * ( - 1 ) * 4 = - 24
( минус * минус = плюс; плюс * минус = минус
минус * плюс = минус знак минус)
( теперь можно все перемножить и поставить знак минус: 3 * 2 * 1 * 4 = 24 и знак минус)
- 3 * ( - 2 ) = 6
6 * ( - 1 ) = - 6
- 6 * 4 = - 24
б) ( -2 ) * 3 * ( -4 ) * ( -6 ) = - 144
( минус * плюс = минус; минус * минус = плюс; плюс * минус = минус)
( 2 * 3 * 4 * 6 = 144 и знак минус)
- 2 * 3 = - 6
- 6 * ( - 4 ) = 24
24 * ( - 6 ) = - 144